Association of Environmental Sanitation and Personal Hygiene Practices with Underweight Among Children Under five - Fitratun Nisa; Hairunnisah Hairunnisah; Alkhair Alkhair; Nur Husnul Khatimah (Universitas Muhammadiyah Palembang, 2026)
Underweight among children under five is a serious nutritional problem that adversely affects children's growth and development. Environmental sanitation and personal hygiene are considered important factors associated with the incidence of underweight. This study aimed to analyze the relationship between environmental sanitation and personal hygiene among children under five and the incidence of underweight in the working area of the Mpunda Community Health Center, Bima City. This study employed a quantitative cross-sectional design. Data were collected using questionnaires and direct field observations. Data were analyzed using the Chi-square test for bivariate analysis and multiple logistic regression for multivariate analysis. The bivariate analysis showed a significant association between environmental sanitation and underweight (p < 0.001; PR = 9.44; 95% CI: 3.59–24.84), as well as between personal hygiene and underweight (p < 0.001; PR = 3.98; 95% CI: 2.05–7.72). The multivariate analysis indicated that environmental sanitation and personal hygiene were significantly associated with the incidence of underweight. Environmental sanitation was identified as the most dominant variable in the analytical model, while personal hygiene was also significantly associated with underweight. Therefore, improving environmental sanitation through the provision of safe drinking water, sanitary latrines, and strengthening parental education on clean and healthy living practices for children under five is essential for preventing underweight.